The molecular mechanism of shade avoidance in crops – How data from Arabidopsis can help to identify targets for increasing yield and biomass production - Yun-jia TANG; Johannes Liesche (Journal of Integrative Agriculture)
In order to prevent or counteract shading, plants enact a complex set of growth and developmental adaptations when they sense a change in light quality caused by other plants in their vicinity. This shade avoidance response (SAR) typically includes increased stem elongation at the expense of plant fitness and yield, making it an undesirable trait in an agricultural context. Manipulating the molecular factors involved in SAR can potentially improve productivity by increasing tolerance to higher planting density. However, most of the investigations of the molecular mechanism of SAR have been carried out in Arabidopsis thaliana, and it is presently unclear in how far results of these investigations apply to crop plants. In this review, current data on SAR in crop plants, especially from members of the Solanaceae and Poaceae families, are integrated with data from Arabidopsis, in order to identify the most promising targets for biotechnological approaches. Phytochromes, which detect the change in light caused by neighboring plants, and early signaling components can be targeted to increase plant productivity. However, they control various photomorphogenic processes not necessarily related to shade avoidance. Transcription factors involved in SAR signaling could be better targets to specifically enhance or suppress SAR. Knowledge integration from Arabidopsis and crop plants also indicates factors that could facilitate the control of specific aspects of SAR. Candidates are provided for the regulation of plant architecture, flowering induction and carbohydrate allocation. Yet to-be-elucidated factors that control SAR-dependent changes in biotic resistance and cell wall composition are pointed out. This review also includes an analysis of publicly available gene expression data for maize to augment the sparse molecular data available for this important species.